Social Marketing Project Pemasaran Produk UMKM Penjahit Rumahan Melalui Media Sosial Pada Usaha Jahit Ibu Noni Di Lempuing Kota Bengkulu - Amelia, Amelia; Prawitasari, Andriyani; Yanti, Rina Trisna; Handayani, Sri; Hanila, Siti (Universitas Dehasen Bengkulu, 2024)
Social marketing marketing projects in a business are very important to develop in a business so that the business can be better known by the public. The aim of this community service in the home sewing business sector is to provide vacancies for sewing business actors so that the businesses they run can get more turnover or jobs from consumers. Methods that can be used to achieve this goal are by helping business people to open their stalls in strategic places and also by opening social media accounts to facilitate product marketing. With the completion of social media creation for business actors, they can immediately jump into loading or sharing some content about the products or services they offer to consumers.